If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 + 30x = 15x + 22 Reorder the terms: 4 + 30x = 22 + 15x Solving 4 + 30x = 22 + 15x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-15x' to each side of the equation. 4 + 30x + -15x = 22 + 15x + -15x Combine like terms: 30x + -15x = 15x 4 + 15x = 22 + 15x + -15x Combine like terms: 15x + -15x = 0 4 + 15x = 22 + 0 4 + 15x = 22 Add '-4' to each side of the equation. 4 + -4 + 15x = 22 + -4 Combine like terms: 4 + -4 = 0 0 + 15x = 22 + -4 15x = 22 + -4 Combine like terms: 22 + -4 = 18 15x = 18 Divide each side by '15'. x = 1.2 Simplifying x = 1.2
| 5x-7x-100=50 | | r-2=2 | | 3(-x-5)=12 | | X-3=5x-41 | | -15+x^2+2x=0 | | 10(c+11)=5t | | -16=-3v+2 | | 9x-9-5x=5x-1 | | -2+3x=-3+4x | | 8x+5=7x+18 | | -3a+3=-18 | | 4x+3=15-3x | | 40k+30=30k+80 | | -4y+19=-14+6y | | 3x-5x-10=-8+5x+4 | | 2x+8=-22-8 | | 7x+6=12x-12 | | 5x+18-4x=-2-10 | | (3x-1)*(4x+3)+(2x+5)*(x-3)= | | 2x+11=x-7 | | 10x+1y=6000 | | 3x+12=-33-6x | | 5r+4j-3r-2j+6= | | .5d-9=2 | | 9m^2+2m=6 | | 4(-3y-1)-3(2y)=6 | | 36y-(-6)=114 | | 5x+21=7x-15 | | (2x^2)-4=16 | | 5z=2.8+3.2 | | f(x)=7(-x)+2 | | 6+4b=b+2b |